2022
DOI: 10.1007/s10549-022-06798-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alpelisib-induced hyperglycemia prophylaxis and associated risk factors in PIK3CA-mutated hormone-receptor positive, human epidermal growth factor-2 negative advanced breast cancer

Abstract: Purpose SOLAR-1 investigated alpelisib-fulvestrant (ALP+FLV) in patients with HR+/HER2-, PIK3CA-mutated advanced breast cancer and demonstrated a clinically signi cant increase in all-grade and grade (G) 3-4 hyperglycemia (HG) compared to placebo-fulvestrant. Given high rates of HG, a preventative protocol and identi cation of associated risk factors was implemented. MethodsThis single-center, retrospective study included patients receiving ALP+FLV. One week before ALP initiation, patients started an insulin-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The inhibition of this pathway can lead to abrogated insulin function, impaired insulin secretion, and the development of insulin resistance, resulting in hyperglycemia 2,4,31 . Previous studies have reported the incidence of hyperglycemia associated with PI3K-AKT-mTOR pathway inhibitors in large phase III clinical trials ranging from 13 to 63.7% and high-grade hyperglycemia from 4 to 32.7% [32][33][34] . The incidence of hyperglycemia may also differ depending on the combination drug, disease stage, and alpelisib dose used.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of this pathway can lead to abrogated insulin function, impaired insulin secretion, and the development of insulin resistance, resulting in hyperglycemia 2,4,31 . Previous studies have reported the incidence of hyperglycemia associated with PI3K-AKT-mTOR pathway inhibitors in large phase III clinical trials ranging from 13 to 63.7% and high-grade hyperglycemia from 4 to 32.7% [32][33][34] . The incidence of hyperglycemia may also differ depending on the combination drug, disease stage, and alpelisib dose used.…”
Section: Discussionmentioning
confidence: 99%